Social Media Network Analysis Of Virtual Public Opinion For Luhut Binsar Panjaitan On Twitter - Khairul Syafuddin (INJECT (Interdisciplinary Journal of Communication), 2022)
The Indonesian people are currently in a situation of rising oil prices. Either in the form of cooking oil or pertamax. This condition makes the public conversation on Twitter very crowded. Especially when news emerged regarding Luhut Binsar Panjaitan signaling that the price of pertalite and 3 kg LPG would also increase gradually. This led to trending topics with the hashtags #OpungBiangKerok and #PecatBrutusLuhut. The theory used in this research is the theory of representation and agenda setting which is carried out in the context of social media. The purpose of this study is to determine the strength of the network on Twitter in shaping public opinion which aims to attack Luhut's image. This study uses a qualitative method. The analytical technique chosen in this study is the analysis of social media networks. The results of this study see that the hashtags #OpungBiangKerok and #PecatBrutusLuhut were produced in 2 different moments. The hashtag #OpungBiangKerok was built when Luhut signaled a price increase. Meanwhile, the hashtag #PecatBrutusLuhut emerged after the student demonstration on April 11, 2022. However, the opinion that was built through the hashtag #PecatBrutusLuhut focused more on Jokowi's 3-term rejection. Through these two hashtags, netizens on Twitter are trying to build a representation of Luhut's image as a leader who is cruel to the people. The community movement is not only strong when in the field, but there is also a strong effort on social media to produce a public opinion. This movement at the same time strengthens their action in the field.